Miss Fisher's murder mysteries. Murder under the mistletoe [videorecording (DVD)] - Davis, Essie; Page, Nathan, 1973-; Johnstone-Burt, Hugo; Greenwood, Kerry (RLJ Entertainment, 2019)
A stylish and sexy period mystery stars Essie Davis as Phryne Fisher, a glamorous lady detective in 1920s Melbourne. In 'Murder under the Mistletoe," Phryne's Christmas in July turns deadly when trapped inhabitants at a snowed-in mountain lodge find themselves being killed off according to the song The Twelve Days of Christmas.